NH3 and N2O Real World Emissions Measurement from a CNG Heavy Duty Vehicle Using On-Board Measurement Systems - Ricardo Suarez-Bertoa; Roberto Gioria; Tommaso Selleri; Velizara Lilova; Anastasios Melas; Yusuke Onishi; Jacopo Franzetti; Fabrizio Forloni; Adolfo Perujo (Applied Sciences, 2021)
The development and utilization of a series of after-treatment devices in modern vehicles has led to an increase in emissions of NH3 and/or N2O with respect to the past. N2O is a long-lived greenhouse gas and an ozone-depleting substance, while NH3 is a precursor of secondary aerosols in the atmosphere. Certain regions, e.g., the EU and the USA, have introduced limits to the emissions of NH3 or N2O for vehicles tested in the laboratory. However, due to the lack of on-board systems that allow for the measurement of these compounds when the regulations were developed, these vehicles’ real-world emissions have not been regulated. This work evaluates on-board systems that could allow measuring real-world emissions of NH3 and N2O from heavy-duty vehicles. In particular, emissions of NH3 or N2O from a Euro VI Step D urban/interurban bus fueled with Compressed Natural Gas were measured using the HORIBA’s OBS-ONE-XL, which is based on a specifically developed technique called Infrared Laser Absorption Modulation, and uses a Quantum Cascade Laser as a light source. They were also measured using the PEMS-LAB, which is a more conventional FTIR-based system. Emissions were measured under real-world driving conditions on the road and in a climatic test cell at different ambient temperatures. For most of the conditions tested, the on-board systems correlated well with a laboratory-grade FTIR used as reference. In addition, a good correlation with R2 > 0.9 was found for the N2O concentrations measured by OBS-ONE-XL and PEMS-LAB during on-road testing.